Metaverse: A real change or just another research area? - Christian Peukert; Hamed Qahri-Saremi; Ulrike Schultze; Jason B. Thatcher; Christy M. K. Cheung; Adeline Frenzel-Piasentin; Maike Greve; Christian Matt; Manuel Trenz; Ofir Turel (Electronic Markets, 2024)
The Metaverse, an evolving concept that fuses physical reality with digital virtuality, offers a dynamic environment for exploration. This paper reports the panel discussion on the Metaverse and its potential implications for individuals and research. This discussion was held at the Digitization of the Individual (DOTI) workshop at the International Conference on Information Systems in December 2022. Four scientists who have researched virtual reality, immersiveness, and corresponding user behavior were invited to the panel discussion. The panelists offered their perspectives on the unique characteristics of the Metaverse, how it differs from earlier digital worlds, and the implications that the Metaverse will bring for individuals. This paper provides an introduction to the emerging phenomenon of “Metaverse” and summarizes the discussion and expert perspectives on the topic. Furthermore, this paper links the discussion to the ongoing discourse in the literature, setting the stage for further investigations by providing explicit research avenues and questions.
Keywords: M00; M15; O32; O33; 620; Metaverse; Virtual reality; Digitization of the Individual (DOTI); Research agenda; Panel